Othello and interpretive traditions - Pechter, Edward, 1941- (Studies in theatre history and culture., 1999)
℗¡During the past twenty years or so, Othello has become the Shakespearean tragedy that speaks most powerfully to our contemporary concerns. Focusing on race and gender (and on class, ethnicity, sexuality, and nationality), the play talks about what audiences want to talk about. Yet at the same time, as refracted through Iago, it forces us to hear what we do not want to hear; like the characters in the play, we become trapped in our own prejudicial malice and guilt.℗¡